Clinical features in antiglycine receptor antibody-related disease: a case report and update literature review - Wu, Xiaoke; Zhang, Haifeng; Shi, Mengmeng; Fang, Shaokuan (Frontiers in Immunology, 2024)
Background and Objectives: Antiglycine receptor (anti-GlyR) antibody mediates multiple immune-related diseases. This study aimed to summarize the clinical features to enhance our understanding of anti-GlyR antibody-related disease.Methods: By collecting clinical information from admitted patients positive for glycine receptor (GlyR) antibody, the clinical characteristics of a new patient positive for GlyR antibody were reported in this study. To obtain additional information regarding anti-GlyR antibody-linked illness, clinical data and findings on both newly reported instances in this study and previously published cases were merged and analyzed.A new case of anti-GlyR antibody-related progressive encephalomyelitis with rigidity and myoclonus (PERM) was identified in this study. A 20-year-old man with only positive cerebrospinal fluid anti-GlyR antibody had a good prognosis with first-line immunotherapy. The literature review indicated that the common clinical manifestations of anti-GlyR antibody-related disease included PERM or stiff-person syndrome (SPS) (n = 179, 50.1%), epileptic seizure (n = 94, 26.3%), and other neurological disorders (n = 84, 24.5%). Other neurological issues included demyelination, inflammation, cerebellar ataxia and movement disorders, encephalitis, acute psychosis, cognitive impairment or dementia, celiac disease, Parkinson's disease, neuropathic pain and allodynia, steroid-responsive deafness, hemiballism/tics, laryngeal dystonia, and generalized weakness included respiratory muscles. The group of RERM/SPS exhibited a better response to immunotherapy than others.The findings suggest the presence of multiple clinical phenotypes in anti-GlyR antibody-related disease. Common clinical phenotypes include PERM, SPS, epileptic seizure, and paraneoplastic disease. Patients with RERM/SPS respond well to immunotherapy.